Beam Splitters Fabricated by Nonlinear Focusing of Femtosecond Laser Writing in Pure YAG Crystal - Wu, Pengfei; Yang, Senchi; Ren, Yingying; Liu, Hongliang (Frontiers in Physics, 2021)
We report on the fabrication of waveguides and beam splitters in pure YAG crystals by femtosecond laser direct writing (FLDW). During the femtosecond laser writing process, a positive refractive index is induced through the nonlinear focusing above the focus position, resulting in an unusual guiding cross-sectional configuration. The supported guiding modes at 632.8 nm are measured and analyzed using the end–face coupling system. The propagation loss can be as low as 1.9 dB/cm for the single-line waveguide. Different from the geometry of the traditional fs-laser modified area, this novel structure might offer a new approach in the quest toward integrated photonics.